Nutrition and Human Oral Health - Vach, Kirstin; Woelber, Johan Peter (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book contains the Nutrients Special Issue "Nutrition and Human Oral Health" edited by Dr. Kirstin Vach and Prof. Dr. Johan Woelber. It includes 18 wonderful publications that provide an outline of current scientific work in the field of nutritional dentistry.